The Role of Village Government Facilitators in Tourism Object - Erdianto, Tria Ilham; Usrotin Choiriyah, Ilmi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and describe the role of the Village Government in the management of Coban Binangun tourism objects in Plintahan Village, Pandaan District, Pasuruan Regency. This research is a qualitative descriptive research using purposive sampling informant determination technique. Data collection techniques through interviews, observation and documentation. The data analysis technique uses the Analysis Interactive Model from Miles and Huberman which consists of four components, namely data collection, data reduction, data presentation and drawing conclusions. The Village Government plays a good role in providing facilities to all parties (Pokdarwis and the Community) in mutual cooperation activities to improve the infrastructure needed for Coban Binangun such as parking lots for motorbikes, toilets and for the benefit of tourists who come to visit Coban Binangun tourism objects, the Village Government only providing facilities in the form of funds only, there is no provision of facilities such as guidance and training on tourism, both its development and management for Pokdarwis and the Plintahan Village Community. The village government also invites the community and all related parties to participate in cooperation in the management of the Coban Binangun tourism object, but so far there has been no private party or private investor who has participated in the management of this tourism object